Studi Tingkat Kepuasan Pasien dan Masyarakat Rawat Inap dan Rawat Jalan Terhadap Pelayanan Kefarmasian di RSUD Teungku Peukanaceh Barat Daya - Ria Ceriana; Hidayati Hidayati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Patient satisfaction is an element that is often used as a benchmark in assessing the quality of service in a hospital, so that every hospital tries to improve the quality of hospital services in order to give a good impression on patients. The quality of pharmacy services in hospitals is very influential on the quality of patient health . Patient health quality is related to the level of patient satisfaction with pharmaceutical services. The purpose of this study was to determine the level of patient and community satisfaction inpatient and outpatient care for pharmacy services in Teungku Peukan Regional Hospital, Aceh Barat Daya. This study used a non-experimental descriptive study, with a population of 200 people, the total sample in this study was 133 respondents. This research was carried out in March to May 2018 in Teungku Peukan Aceh Barat Southwest Hospital. How to collect data by distributing questionnaires to respondents. Patient satisfaction is assessed from the results of questionnaires which are viewed from 5 Servqualya dimensions namely Reliability, Responsiveness, Assurance, Empathy, and Tangibles. Satisfaction level analysis was carried out by calculating the average performance and expectations. The results showed that the average value of satisfaction and expectations suitability> 75% in each dimension namely 94.90% reliability, 91.17% responsiveness, 90.59 certainty %, empathy 93.54%, and tangible 89.82%. So, the level of patient and community satisfaction inpatient and outpatient care for pharmacy services in RSUD Teungku Peukan Aceh Barat Daya is satisfied. Patients and the community are satisfied with the services provided by the pharmacy installation staff of Teungku Peukan Aceh Barat Daya